Among Absences - Gabriela Coronado (PORTAL: Journal of Multidisciplinary International Studies, 2011)
Utilizando el género epistolar, una carta a mi madre, reflexiono sobre mi nueva vida e identidad como emigrante en Australia explorando mis percepciones sobre la diferencia cultural y lingüística. Lejos de mis hijas y nietos en México, en esta carta, tardíamente escrita, relato mis recuerdos, nostalgias y vivencias en el nuevo ambiente, y sobre todo, hablo de mis dificultades para manejar emocionalmente mi miedo a la ausencia en los momentos importantes del ciclo de vida, la enfermedad y la muerte.

Using the epistolary genre, a letter to my mother, I reflect on my life and identity as an emigrant in Australia by exploring my perceptions of cultural and linguistic difference. Far from my children and grandchildren in Mexico, in this belatedly written letter I recall my memories, nostalgic feelings and expereinces in the new environment, and above all, I speak of my difficulties in mangaing emotionally my fears of being absent in the important moments of the cycle of life, sickness and death.